Próba rekonstrukcji zmian roślinności w okolicach osady kultury pomorskiej w Odrach na podstawie źródeł przyrodniczych (podsumowanie wstępnej fazy badań) - Grzelakowska, Elżbieta (Acta Universitatis Lodziensis. Folia Archaeologica, 1990)
In 1986 the Archaeological Department of University of Łódź conducted excavations in the settlement of Pomeranian culture site 2.This site has been already known from very few records describing the previoue rescue investigations (from 1926 and 1962). Two settlement phases were distinguished on it: the first one related to the settlement of the culture of funnel-shaped wine-cups and the other one to Pomeranian culture. The archaeological-natural studies led nowadays aim at identification of settlement processes on the backround of changes in the natural environment.The present paper attempts to summing up the first stage of investigations. It includes facts known from archaeological sources and natural studies conducted so far (palinologic and pnlaeobotanical) which indicated on existing relationships among climatic changes, habitat conditions and recorded material traces of the settlement.